PENDIDIKAN ISLAM PERSPEKTIF AL-GHAZALI DALAM MENGATASI SOSIAL DISORDER DI ERA DISRUPTIF - Chusnul Muali; Nur Hidayati (Nurul Jadid University, 2020)
This research aims to provide an overview of the urgency of Islamic education as a shield from the problem of social disorder in humans. Islamic education has a very strategic position in the development of human nature. Therefore, the study of education has attracted many experts, one of them is Al-Ghazali. In his theory, introducing that one of the substances of education is al-aql (thinking) can determine human thinking that leads to positive or negative things depending on someone who reacts. The research used a descriptive-analytical type. With content analysis techniques. This research uses a library research type approach. The results show that Islamic education in the disruptive era is able to overcome the social disorders that exist in society. It is realized that Social disorder is a pest in people's lives that has side effects on a person, so it is not able to explore itself given the disruptive era brought a lot of progress in the field of science and technology.